Poverty among Cotton Producers : Evidence from West and Central Africa - Tsimpo, Clarence; Wodon, Quentin (World Bank, Washington, DC, 2012)
In many sub-Saharan African countries household surveys are well designed to measure consumption and poverty as well as human development outcomes (especially in education and health) and access to basic infrastructure. But detailed information on the sources of income and the livelihoods of households and individuals are still often lacking. This is problematic because income data is essential to identify the links between growth and poverty reduction, to determine ways to improve household well-being, and to understand the potential impacts of economic shocks and policy reforms. In a context where countries as well as international organizations such as the World Bank are asked to document the potential poverty and social impact of the reforms that they propose (through Poverty and Social Impact Analysis), it is important to encourage countries to start collecting data or to improve data collection on income sources.